Differences in Emotion Regulation Considering Gender, Age, and Gambling Preferences in a Sample of Gambling Disorder Patients - Sancho, Marta; de Gracia, Marta; Granero, Roser; González-Simarro, Sara; Sánchez, Isabel; Fernández-Aranda, Fernando; Trujols, Joan; Mallorquí-Bagué, Núria; Mestre-Bach, Gemma; del Pino-Gutiérrez, Amparo; Mena-Moreno, Teresa; Vintró-Alcaraz, Cristina; et al. (Frontiers in Psychiatry, 2019)
Introduction: Impairments in emotion regulation are understood to be a transdiagnostic risk factor of suffering from compulsive and addictive behaviors. The aim of this study was to investigate the role of emotion regulation deficits in gambling disorder and to analyze these differences taking gender, age and gambling activity preferences into account. Methods: The sample included n=484 patients seeking treatment for gambling disorder at a specialized outpatient service. Main outcomes were socio-demographic variables, emotion regulation and gambling severity. Results: Differences between sexes were found in non-acceptance of emotions. Older patients obtained higher levels in non-acceptance of emotions, lack of emotion regulation strategies, emotional clarity and global emotion regulation scores. No differences were found in emotion scores considering gambling preferences (non-strategic versus strategic). Path-analysis showed that emotion regulation scores and age obtained a direct effect on gambling disorder severity, while emotion regulation and gambling preference were not mediational variables in the relationships between gender and age with gambling severity. Conclusions: Emotion regulation impairments differ in patients seeking treatment for gambling problems. Early prevention and intervention programs should incorporate the different dimensions of this process, taking into account clinical phenotypes.